Synthesis of high-mannose oligosaccharides containing mannose-6-phosphate residues using regioselective glycosylation. (September 2018) - Meng, Bo; Wang, Jun; Wang, Quanli; Serianni, Anthony S.; Pan, Qingfeng
Abstract: Molecular recognition of mannose-6-phosphate (M6P)-modified oligosaccharides by transmembrane M6P receptors is a key signaling event in lysosomal protein trafficking in vivo . Access to M6P-containing high-mannose N -glycans is essential to achieving a thorough understanding of the M6P ligand–receptor recognition process. Herein we report the application of a versatile and reliable chemical strategy to prepare asymmetric di-antennary M6P-tagged high-mannose oligosaccharides in >20% overall yield and in high purity (>98%). Regioselective chemical glycosylation coupled with effective phosphorylation and product purification protocols were applied to rapidly assemble these oligosaccharides. The development of this synthetic strategy simplifies the preparation of M6P-tagged high-mannose oligosaccharides, which will improve access to these compounds to study their structures and biological functions. Graphical abstract: Image 1 Highlights: One of few studies on synthesis of mannose-6-phosphate containing oligosaccharides, suitable for rapid library assembly. Complete 1D and 2D NMR analysis of mannose-6-phosphate containing oligosaccharides with high resolution. Combined column purification of mannose-6-phosphate containing oligosaccharides for high purity over 98%.